Deadlock-Free Channels and Locks - Leino, Rustan; Zurich), Peter Müller (ETH; Leuven), Jan Smans (KU (ESOP 2010, Paphos, Cyprus, 2010)
The combination of message passing and locking to protect shared state is a useful concurrency pattern. However, programs that employ this pattern are susceptible to deadlock. That is, the execution may reach a state where each thread in a set waits for another thread in that set to release a lock or send a message. This paper proposes a modular verification technique that prevents deadlocks in programs that use both message passing and locking. The approach prevents deadlocks by enforcing two rules: (0) a blocking receive is allowed only if an-other thread holds an obligation to send and (1) each thread must perform acquire and receive operations in accordance with a global order. The approach is proven sound and has been implemented in the Chalice program verifier.